Le verbe «pouvoir» au passé composé et les relatiońs aspect/modalité - Kuszmider, Barbara (Studia Romanica Posnaniensia, 2003)
The aim of this paper is to specify some of the relations between modal domain and aspect. In French, verbal aspect is strictly linked to the past tense. That is why we propose an analysis of sentences with pouvoir in passe compose. Several typological-grammatical categories implicated in the modal interpretation are examined. Thus, considerable restrictions on person, interrogation or semantic property of the verb are identified in the functioning of the two main types of modality, deontic and epistemic.